(untitled) (Communication & Society, 2009)
In this article, the BBC’s funding resources are studied. A relevant analysis because of the digital television challenge which will allow –among other several things– a wide range of channels. The survival and types of contents of public corporations will mainly depend on their financial systems. For that reason, it is important to know the financial model of the one of the public corporation more successful in the world. Firstly, the advantages and disadvantages of the three economic resources of the BBC will be analyzed: licence-fee, commercial activities and grant-in-aids. Later, other funding resources not related to the BBC will be taken into consideration, as advertising and subscription. Finally, the BBC’s funding system will be assessed.